The Effect of Anthrax Bioterrorism on Emergency Department Presentation - Rodriguez, Robert M; Reeves, Jabari; Houston, Sherard; McClung, Christian (Western Journal of Emergency Medicine, 2005)
Study Objective: From September through December 2001, 22 Americans were diagnosed with anthrax, prompting widespread national media attention and public concern over bioterrorism. The purpose of this study was to determine the effect of the threat of anthrax bioterrorism on patient presentation to a West Coast emergency department (ED). Methods: This survey was conducted at an urban county ED in Oakland, CA between December 15, 2001 and February 15, 2002. During random 8-hour blocks, all adult patients presenting for flu or upper respiratory infection (URI) symptoms were surveyed using a structured survey instrument that included standard visual numerical and Likert scales. Results: Eighty-nine patients were interviewed. Eleven patients (12%) reported potential exposure risk factors. Eighty percent of patients watched television, read the newspaper, or listened to the radio daily, and 83% of patients had heard about anthrax bioterrorism. Fifty-five percent received a chest x-ray, 10% received either throat or blood cultures, and 28% received antibiotics. Twenty-one percent of patients surveyed were admitted to the hospital. Most patients were minimally concerned that they may have contracted anthrax (mean=3.3±3.3 where 0=no concern and 10=extremely concerned). Patient concern about anthrax had little influence on their decision to visit the ED (mean=2.8±3.0 where 0=no influence and 10=greatly influenced). Had they experienced their same flu or URI symptoms one year prior to the anthrax outbreak, 91% of patients stated they would have sought medical attention. Conclusions: After considerable exposure to media reports about anthrax, most patients in this urban West Coast ED population were not concerned about anthrax infection. Fear of anthrax had little effect on decisions to come to the ED, and most would have sought medical help prior to the anthrax outbreak.